Cellulose nanofibers isolation and characterization from ramie using a chemical-ultrasonic treatment - Edi Syafri; Anwar Kasim; Hairul Abral; Alfi Asben (Journal of Natural Fibers, 2019)
The novelty of this work lies in isolating cellulose nanofibers from ramie (Boehmerianivea (L.) Gaud) using chemical-ultrasonication treatment. The cellulose nanofibers were successfully isolated from ramie with a diameter and length of 9.9–89.1 nm and 1 μm, respectively. The samples were characterized by scanning electron microscopy, transmission electron microscopy, particle size analysis, Fourier transform infrared spectroscopy, X-ray diffraction analysis, and thermogravimetric analysis. Indeed, there is a decrease in the hemicellulose and lignin content while the cellulose content increases due to the pulping and bleaching processes. The chemical-ultrasonication treatment results in a high yield of cellulose nanofibers (89.35%).